IMPLEMENTATION OF THE REAL WORK LECTURE (KKN) PROGRAM FOR STUDENTS OF GUNUNG JATI INDEPENDENT UNIVERSITY ON THE ASPECTS OF EDUCATION, ENVIRONMENT, LAW, AND HEALTH IN PANUNGGUL VILLAGE, GEGESIK DISTRICT - Dea Triasari Indriyanti Wahidin; Auliya Fasya Nur Salsabila; Vanessa aYesika; Purnama Aji; Ikhsan Mustakim (Ann Publisher, 2026)
Background. Real Work Lecture (KKN) is a form of community service activities carried out by students as part of the implementation of the Tri Dharma of Higher Education. Aims. This activity aims to make a real contribution to the community through a range of educational and empowerment programs. The KKN program for students of Swadaya Gunung Jati University was conducted in Panunggul Village, Gegesik District, with a focus on activities in education, environment, law, and health. Methods. The method used in this activity is a participatory approach through field observation, socialization, counseling, and the implementation of work programs that directly involve the community. In education, activities include tutoring and teaching elementary school students to increase understanding and interest in learning. Result. In the environmental field, students provide education on waste decomposition through a plan. In the field of law, students educate the public on the importance of legal awareness to ensure harmonious family relationships and to prevent and combat domestic violence (KDRT). Meanwhile, in the health sector, health counseling and free health check-up activities were carried out as an effort to increase public awareness of the importance of maintaining health. Conclusion. . The results of this KKN activity indicate an increase in knowledge and community participation across education, the environment, law, and health. Through this activity, it is hoped that students can play an active role in addressing community problems and providing sustainable benefits for the residents of Panunggul Village.